2021
DOI: 10.1038/s41379-020-00731-4
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency (HRD) score in germline BRCA2- versus ATM-altered prostate cancer

Abstract: The homologous recombination deficiency (HRD) score integrates three DNA-based measures of genomic instability, and has been understudied in prostate cancer. Given the recent FDA-approval of two PARP inhibitors for prostate cancer, HRD score analysis could help to refine treatment selection. We assessed HRD score (defined as the sum of loss-of-heterozygosity, telomeric allelic imbalance, and large-scale state transitions) in three cohorts of primary prostate cancer, including a Johns Hopkins University (JHU) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 48 publications
(70 reference statements)
7
56
0
Order By: Relevance
“…Recently, in prostate cancer, TP53 mutations were reported to be associated with increased HRD scores independently of HRR pathway gene alterations. 40 This suggests that high HRD score in TP53 -mutated cases could alternatively be because of chromosomal instability caused by mechanisms other than HRD (eg, loss of cell-cycle checkpoint mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in prostate cancer, TP53 mutations were reported to be associated with increased HRD scores independently of HRR pathway gene alterations. 40 This suggests that high HRD score in TP53 -mutated cases could alternatively be because of chromosomal instability caused by mechanisms other than HRD (eg, loss of cell-cycle checkpoint mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…They found HRD score was higher for tumors with germline mutations in these genes than tumors with wildtype genes. Interestingly, HRD score was highest for germline mutations in BRCA2 , followed by ATM and CHEK2 , consistent with the OR of germline mutations in these different genes 22 . For HOXB13 , the lack of deletion or protein truncating mutations suggest a gain‐of‐function may contribute to the development of PCa 23,24 …”
Section: Discussionmentioning
confidence: 54%
“…3A). In a very recent study of prostate cancer, TP53 mutations were reported to be associated with increased HRD scores independently of HRR pathway gene alterations 57 . These observations suggest that the high HRD score in TP53 mutated cases is not necessarily due to true HRD but, rather, due to chromosomal instability caused by mechanisms other than HRD (e.g., loss of cell-cycle checkpoint mechanisms).…”
Section: Discussionmentioning
confidence: 99%